Representing prison life: criminal creativity in the imperial and soviet eras - Young, SJ
The essay explores how the position and representation of the criminal world, an area frequently posited as indicating a radical break between the pre-revolutionary and Soviet penal systems, in fact becomes a source of continuities, through the recurring theme of the criminal as poet, verbal artist and literary connoisseur. Two distinct strands are identified in the development of the idea of criminal creativity: the verbal antics of Dostoevskii's peasant-convicts are connected to the construction of Siniavskii-Terts's Golos iz khora, which uses the prisoners' utterances to contextalize his own meditations on artistic subjects, while Doroshevich's exploration of the morality of 'poet-murderers' on Sakhalin prefigures the violence of Shalamov's depiction of the criminal world in Kolyma, in which creativity engenders destruction. Comparing these opposing approaches, the paper examines the ways in which in both cases the theme becomes the basis for reflection on wider questions surrounding relationships between criminals, political convicts, and camp/prison authorities, and a commentary on conditions and the impact of the system upon its inhabitants.